Differences in marital quality between full-time and bivocational pastors in the church of the Nazarene - Hayes, Everett C. (Kansas State University, 2010)
The purpose of this study was to determine if there was a difference in marital quality between full-time and bivocational pastors and their spouses in the Church of the Nazarene. While the denomination is a world-wide organization this study only considered clergy couples in the United States of America. The denomination has seventy-five districts in the United States. Originally, ten districts were randomly selected, however, due to a low response rate; five additional districts were purposely selected based on the availability of email addresses for the pastors. A mailing was sent to senior pastors and their spouses from the original ten districts. E-mails were sent to senior pastors and their spouses from all fifteen districts. A link was included in the e-mail that directed the individual to the K-State On-line Survey System. From the mail and the e-mail there were one hundred and ninety-nine responses. The survey included the following instruments: the Clergy Family Life Inventory, the Ministry Demand Inventory (Impact and Times), the Kansas Marital Satisfaction Scale, and the Reduced Sound Marital House. Qualitative questions were also asked according to the individuals’ position (i.e. Full-time Pastor, Full-time Pastor’s Spouse, Bivocational Pastor, Bivocational Pastor’s Spouse). There were six propositions developed for this study, these were: demands of the ministry have a negative effect on marital quality; intrusive congregational expectations have a negative effect on marital quality; the pastor’s own expectations for his/her work with the church will have an effect on his/her marital quality; financial stress will have an adverse effect on marital quality; marital quality is adversely affected when the spouse works outside of the home in order to meet the family budget; and, accepting the influence of his/her spouse has a positive affect on marital quality. Only the last proposition was confirmed. The findings suggest that there is no difference in marital quality between full-time and bivocational clergy couples. However, the reader most also consider the phenomena of social desirability in the context of this research.
Keywords: Clergy marriages; Nazarene; Psychology, General (0621); Sociology, General (0626)